MODELLING INDONESIAN OIL AND GAS EXPORT - Syahnur, Sofyan; Nawafil (Economic Journal of Emerging Markets, 2014)
This study investigates factors affecting Indonesian oil and gas export to six main importing countries. A simultaenuous equation model containing demand and supply equation is used to analyze the problem. A two-stage least squares method is employed to estimate the model. The results show that exchange rate does not statistically influence Indonesian oil and gas export demanded. It also finds that the Gross Domestic Product (GDP) of importing countries and Indonesian oil and gas price statistically affect the demand. From the supply model analysis, price statistically affects Indonesian oil and gas export supplied. In addition, Indonesian oil and gas production influences the supply. Keywords: Oil and gas export, simultaneous equation model, exchange rate, GDP. JEL classification number: F40, Q41 Abstrak Studi ini menyelidiki faktor-faktor yang mempengaruhi ekspor minyak dan gas Indonesia ke enam negara importir utama. Model permintaan dan penawaran digunakan untuk menganalisis ekspor migas Indonesia dalam bentuk persamaan simultan. Metode Two-Stage Least Squares (2SLS) dipakai untuk mengestimasi persamaan simultan tersebut. Hasil studi menunjukkan bahwa kurs tidak berpengaruh terhadap permintaan ekspor migas Indonesia. Studi ini juga menemukan bahwa Produk Domestik Bruto (PDB) negara pengimpor dan harga migas Indonesia berpengaruh terhadap permintaan ekspor migas Indonesia. Dari hasil analisis model penawaran didapatkan bahwa harga dan produksi migas Indonesia mempengaruhi penawaran ekspor migas Indonesia. Kata Kunci: Ekspor minyak dan gas, model persamaan simultan, kurs, PDB JEL classification numbers: F40, Q41